Halal product guarantee system in powdered goat milk production house - Khairani, Wilda Sabrina; Hidayah, Nurul (Universitas Ahmad Dahlan, 2024)
The halal product guarantee system is a criterion that must be met in halal certification activities in order to guarantee and maintain the consistency of the halal product process so that it complies with applicable laws. Processing of powdered goat milk is carried out by adding granulated sugar and vegetable creamer to powdered goat milk products, which in the Decree of the Head of BPJPH No. 748 of 2021 includes critical materials that must have a halal certificate. The decree of the Head of BPJPH No. 57 of 2021 is a reference for the food processing industry. This practical work report aims to determine whether there are critical ingredients in the product and the efforts made in implementing the halal assurance system at powdered goat milk production houses. The problem-solving methodology used is observation, problem formulation, interviews, literature study, documentation, and checklist forms with evaluation criteria referring to the Decree of the Head of the Halal Product Guarantee Agency No. 57 of 2021. The evaluation results show that powdered goat milk production houses have implemented 74.2% of the criteria, and 25.8% of the criteria that have not been met are caused by the negligence of the workforce who do not use masks and gloves; the majority of production processes still use manual methods and a hot room.